فهم السنة النبوية بين المنهج الشرعي والمنهج الهرمنيوطيقي (مجلة الواحات للبحوث والدراسات, 2023)
ملخص:يوازن هذا البحث بين منهجين لفهم السنة النبوية الأول المنهج الشرعي الكلاسيكي، والآخر المنهجي الهرمنيوطيقي التأويلي، وبعد أن يستعرض مفاصل المنهج الأول وعناصره العبارية والإشارية، ينتقل لمفهوم المنهج الثاني ونشأته وتطوره، ثم يقارن بين الاستعمالين في السنة النبوية.خلصت نتيجة الموازنة إلى أن المنهج الشرعي منهج منضبط جدا ومتسم بالاتساق مع نفسه ومع كتابه لاستمرار لغة القرآن في التداول إلى اليوم، بخلاف المنهج الآخر الذي لم يحل مشكلة لغة الكتاب المقدس التي كُتب بها وعانى من انقراض اللغات الوسيطة بين اللغة الأصلية واللغات الحالية التي يتداول بها.كما خلص البحث إلى أن مناورة الحداثيين في توظيف التفسير الإشاري والتصرفات النبوية وتغير الفتوى بتغير الزمان هي مناورة فاشلة لأن كل هذه المفاهيم تستصحب تعظيم القرآن والسنة وتعتقد أنه وحي معصوم، بخلاف المنهج الهرمنيوطيقي الذي يشكك -على الأقل- في هذه القناعة. كلمات دالة: حداثة، هرمنيوطيقا، تأويلية، مقاصد شريعة، تفسير إشاري      Abstract: This Research Balances Two Approaches To Understand The Prophetic Sunnah, The First Is The Classical Islamic Approach, And The Second Is The Hermeneutical Interpretational Approach. After Reviewing The Branches Of The First Approach And Its Phrasal And Semantic Elements, We Move On To The Concept Of The Second Approach And Its Emergence And Development. Then We Compare The Two Uses In The Prophetic Sunnah.The Result Of The Comparison Concluded That The Islamic Approach Is Very Disciplined And Consistent With Itself And With His Book Due To The Fact That The Language Of The Qur'an Continued To Circulate To This Day, Unlike The Other Approach That Did Not Solve The Language Problem Of The Bible In Which It Has Been Written With, And It Suffered The Extinction Of Intermediate Languages Between The Original Language And The Current Languages That Are Used In It.The Research Also Concluded That The Modernist's Maneuver In Employing The Semantic Interpretation And Prophetic Behaviors, In Addition To The Change Of Fatwa By Time Change Is A Failed Maneuver Because All These Concepts Are Associated With The Glorification Of The Qur'an And Sunnah And It Believes That Qur’an Is An Infallible Revelation, Unlike The Hermeneutical Approach, Which At Least Questions This Conviction.Key Words: : Modernity, Hermeneutics, Interpretation, Purposes Of Sharia, Semantic Interpretation.